A simplified elastic composite floor section analysis with incomplete interaction - Ehsan Ahmed; Wan Hamidon Wan Badaruzzaman; Khalim Rashid (1996)
This paper presents a simplified partial interaction elastic analysis of composite floor panels. A theoretical analysis is carried out on repeating section composing of two elastic beam elements connected longitudinally by linearly elastic connection. The analysis is based on the assumption that a continuous imperfect connection exists between the two separate elements. By applying method of elastic equivalence, expressions for stiffness along the major axis of such composite section is developed. Results obtained from the authors' full scale experimental studies involving profiled steel sheet/dryboard composite floor panels are compared with results obtained from the simplified expressions, and with theoretical results obtained by other researchers. It is concluded that these expressions are able to predict with reasonable accuracy the behaviour of composite floor panels